1982
DOI: 10.1007/bf00252847
|View full text |Cite
|
Sign up to set email alerts
|

Digestible carbohydrate ? an independent effect on diabetic control in type 2 (non-insulin-dependent) diabetic patients?

Abstract: Many studies have shown high carbohydrate, high fibre diets to benefit diabetic control, the improvement being attributed mainly to an effect of fibre. This study investigated the possible beneficial effects of the digestible carbohydrate component. A diet rich in carbohydrate was compared with a traditional low carbohydrate diet in 10 Type 2 (non-insulin-dependent) diabetic patients, using a crossover design; both diets contained less than 20 g dietary fibre/day. During 24-h metabolic profiles carried out aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 22 publications
(32 reference statements)
2
25
0
Order By: Relevance
“…Addition of purified viscous fiber to metabolic diets resulted in reduced urinary losses of glucose and ketone bodies (25). The results of these studies have been confirmed by others (26)(27)(28)(29)(30)(31).…”
Section: Historical Notesupporting
confidence: 57%
“…Addition of purified viscous fiber to metabolic diets resulted in reduced urinary losses of glucose and ketone bodies (25). The results of these studies have been confirmed by others (26)(27)(28)(29)(30)(31).…”
Section: Historical Notesupporting
confidence: 57%
“…This is surprising, given that in the late 1980s, it had been clearly shown that high carbohydrate diets were only associated with beneficial effects in terms of glycaemic control and blood lipids when carbohydrate was derived principally from foods rich in soluble forms of dietary fibre, notably pulses, legumes and intact fruits and vegetables (Rivellese et al, 1980;Simpson et al, 1981;Riccardi et al, 1984;Mann, 2001). Higher intakes of cereal (insoluble) fibre were associated with less marked or no benefit in glucose or lipid levels (Simpson et al, 1979;1982;Riccardi et al, 1984). The beneficial effects of soluble forms of dietary fibre derived from fruits and vegetables appear to have been rediscovered more recently in randomized crossover studies in type II diabetes (Chandalia et al, 2000).…”
Section: Experimental Studiesmentioning
confidence: 99%
“…In fact such observations were not entirely new, similar observations having been made many years earlier by Kempner using his rice diet (Kempner et al, 1958). Inspired by the work of Anderson and also by the studies of Stone and Connor (1963), who drew attention to the potential of the low carbohydrate -high fat diet, then in widespread use, to increase cardiovascular risk, our own group in Oxford, England embarked on a series of carefully controlled studies which helped to further understand the role of dietary fibre (Simpson et al, 1979a;Simpson et al, 1979b;Simpson et al, 1981;Simpson et al, 1982;Lousley et al, 1984;Geekie et al, 1986;Mann, 1984). Each of the studies involved a crossover design in which patients with type 1 and type 2 diabetes were randomised to receive advice regarding the standard diabetic diet of the time, relatively low in carbohydrate and dietary fibre, or an experimental high carbohydrate diet.…”
mentioning
confidence: 64%
“…The improvement was particularly striking when foods rich in soluble fibre were encouraged (Simpson et al, 1981). The early studies were criticised on the grounds that we could not distinguish between the beneficial effects of carbohydrates per se and dietary fibre, but later studies in which carbohydrate alone was increased left little doubt that in order to achieve improved glycaemic control and reduced LDL without any increase in VLDL and triglycerides or reduction in HDL it was essential to increase dietary fibre, especially soluble fibre (Simpson et al, 1982). We were also able to show that it was possible to achieve beneficial effects with more acceptable amounts of dietary fibre than had been used in our earlier studies (Lousley et al, 1984).…”
mentioning
confidence: 99%